Association between tea drinking and disability levels in older Chinese adults: a longitudinal analysis - Ma, Yinghui; Zhu, Yuying; Hong, Dandan; Zhao, Haiyue; Li, Lei (Frontiers in Nutrition, 2023)
Objective: As the global population ages, disability among the elderly presents unprecedented challenges for healthcare systems. However, limited research has examined whether dietary interventions like tea consumption may alleviate and prevent disability in older adults. As an important dietary therapy, the health benefits of tea drinking have gained recognition across research disciplines. Therefore, this study aimed to investigate the association between tea drinking habits and disability levels in the Chinese elderly population.